Knowledge, Attitude And Practice Regarding Vitamin D Deficiency Among Antenatal Mothers In Tamilnadu - DURAIRAJ KAVITHA; CHANDRASEKAR ANJALAKSHI; PRABHU VENKATARAMAN; JANAKIRAMAN RUKUMANI; MURALI (International Journal of Pharma and Bio Sciences, 2015)
Our main aim is to explore the knowledge, attitude and practice of vitamin D supplementation among pregnant mothers. The study design is descriptive study and was carried out in Antenatal Out Patient Department, SRM Medical College Hospital and Research Centre, Kattankulathur, Tamilnadu. Eighty six (86) Samples were selected by simple purposive sampling technique between May to November 2014. Structured questionnaire was used to collect the data from samples. The collected data was analyzed by using descriptive statistics. Result showed Forty-eight (48%) of antenatal mothers were in the group of 26 to 30 years. Thirty nine (39%) had studied up to graduate level. Most of them were house maker (86%). Ninety three (93%) of them were joint family. Thirty three (33%) had monthly income of Rs.15188-30374. Majority of them ninety two (92%) were non vegetarian. Sixty seven (67%) of them are primi mothers. None of them were taking vitamin D supplements during antenatal period. 43% of them were using a cosmetic cream containing sun protection factor (SPF) more than 8, without their knowledge. Fifty three (53%) of them got knowledge of vitamin D from the books and magazine. The majority of subjects forty four (44%) were able to recognize sunshine as a source of vitamin D and forty eight (48%) of the subjects did not know the source of the vitamin D. The majority of the study participants had limited knowledge, poor practices, and did not have positive attitude towards benefits of vitamin D supplements. To improve in this situation mother should be educated about importance of vitamin D in planned health education interventions.